Analysis of Mangrove Forest Management in Teluk Lembar, West Lombok, Indonesia - Muhammad Al’Awali Salahuddin; Nyoto Santoso; Rachmad Hermawan (Postgraduate, University of Mataram, 2024)
Mangrove forests in Teluk Lembar, West Lombok, have an important role in ecological balance and socio-economic benefits. However, these ecosystems face pressure from land conversion for ponds, illegal logging, and pollution. This study aims to describe the condition of mangroves, analyze the socio-economic aspects of the community and the role of stakeholders, assess the value of direct benefits of mangroves, and formulate sustainable management strategies. The results showed significant biodiversity, with 14 species of mangroves and 53 species of fauna, including 44 species of birds. The bird ecological index showed diversity (H') 32, uniformity (E) 0.8, and dominance (D) 0.7, which signified ecosystem stability. However, a serious threat comes from the conversion of land for ponds, houses, factories, and ports. Of the 1703.19 ha of the total area area, only 179.44 ha (10.54%) of mangrove forests remain. Waste pollution, such as mercury and copper levels that exceed the limit, also negatively impacts the ecosystem. Based on the SWOT analysis, the proposed mangrove management strategy includes: (a) strengthening community capacity in mangrove management through training and education, (b) increasing collaboration between stakeholders to strengthen regulation and law enforcement, (c) optimizing economic benefits through the development of mangrove-based ecotourism, and (d) implementing sustainable management practices to maintain a balance between conservation and utilization